Development of quantum dot fluorescence sensors for detection of targeted pesticides & polycyclic aromatic hydrocarbons - Forbes, Patricia B.C. (University of Pretoria, 2020)
Thesis (PhD (Chemistry))--University of Pretoria, 2020.